2017
DOI: 10.1097/sla.0000000000001946
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Value of a Clinical Practice Guideline for Children With Perforated Appendicitis

Abstract: An evidence-based CPG increased the value of surgical care for children with perforated appendicitis by improving outcomes and lowering costs. Hospital cost accounting data and pre-existing cost data within the PHIS database provided similar results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“… 59 Current standard of care and practice guidelines advocate for the early initiation of antibiotics in treatment algorithms. 32 , 62 65 After initiation of antibiotics, treatment options diverge into operative management or non-operative management with or without interval appendectomy. Although there continues to be extensive debate regarding the merits of each treatment option, this review will highlight the indications for each option and propose an algorithm to assist with treatment decisions.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“… 59 Current standard of care and practice guidelines advocate for the early initiation of antibiotics in treatment algorithms. 32 , 62 65 After initiation of antibiotics, treatment options diverge into operative management or non-operative management with or without interval appendectomy. Although there continues to be extensive debate regarding the merits of each treatment option, this review will highlight the indications for each option and propose an algorithm to assist with treatment decisions.…”
Section: Managementmentioning
confidence: 99%
“…Although the diagnosis and management of perforated appendicitis remains complex and controversial, guidelines exist and have been demonstrated to both improve patient outcomes and decrease resource utilization. 31 , 32 , 62 64 Although clinician experience is the best tool in making an accurate diagnosis, 5 , 21 , 36 laboratory studies and selective imaging should be utilized to assist in diagnosis. After a diagnosis of perforated appendicitis is made, all patients should be placed nil per os and started on appropriate broad-spectrum IV antibiotics.…”
Section: Managementmentioning
confidence: 99%
“…Acquisition of patient-level cost data by surgeons is difficult in most healthcare systems as costs are either not available or aggregated over time or departmentally, rather than provided at the patient-level. [1, 8, 13, 14] We have previously shown that institution of a clinical practice guideline (CPG) for perforated appendicitis resulted in a decrease in variability of care, improvement in clinical outcomes, and decrease in overall cost of care. [14, 15] This CPG did not incorporate any intraoperative changes, such as standardization of OR equipment or incentives for OR cost reduction.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize practice variation, optimize healthcare resources, and avoid unnecessary treatments, evidence-based clinical practice guidelines for children with appendicitis have been developed. [2][3][4][5][6][7][8][9] However, despite the advantages of improving outcomes and lowering costs, the guidelines produced by various associations and institutions have not unanimously been accepted. For instance, in 2010, the Dutch Society of Surgeons introduced guidelines that recommended the routine use of ultrasound and/or computed tomography (CT) for the diagnosis of acute appendicitis.…”
Section: Introductionmentioning
confidence: 99%